Optimistic Outlook on the Wellbeing of Teachers: Understanding Mental Health Literacy and Burnout Mitigation - Oliveros, Sugar Timberly Rose; Udtohan, Genevive; Tasan, Renato; Malabago, Nolasco; Neri, Remcil (International Journal of Educational Studies, 2025)
This study investigates the relationship between teachers' mental health literacy and their levels of burnout in public elementary schools. It explores key demographic and professional characteristics, mental health literacy, and burnout dimensions, including emotional exhaustion, depersonalization, workload stress, and reduced personal accomplishment. The teacher profile reveals that the majority have 1-5 years of service, with a significant portion pursuing advanced education. Most teachers are married, highlighting a young and educated workforce balancing professional and personal responsibilities. Findings indicate that teachers possess strong mental health literacy, as evidenced by positive attitudes toward stigma reduction, accessing help, self-awareness, and mental health first aid skills. Despite this, burnout remains a concern, with emotional exhaustion, depersonalization, and workload stress notably affecting their well-being. Reduced personal accomplishment also highlights areas of diminished motivation and job satisfaction. The analysis reveals no significant relationship between mental health literacy and burnout, as all constructs stigma reduction, accessing help, self-awareness, and mental health first aid skills show low r-values and high p-values across burnout dimensions. This suggests that while mental health literacy is crucial for general well-being, factors such as workload and systemic pressures likely play a greater role in teacher burnout. The study concludes that enhancing mental health literacy is essential but must be paired with strategies addressing broader challenges to effectively reduce burnout and support teachers’ well-being and effectiveness.